Consumer Ethnocentrism, Product Knowledge, and Brand Identity on Purchasing Decisions on Eiger Products - Wulandari, Suci; Pebrianggara, Alshaf; Indayani, Lilik (Jurnal Ilmu Manajemen Advantage, 2025)
This research intends determine the impact Consumer Ethnocentrism, Product Knowledge, and Brand Identity on the purchase decision of Eiger products. Elementary study based on the increasing busines competition in the fashion and lifestyle, including in the outdoor equipment sector operated by Eiger. The research method using is quantitative with purposive sampling approach engage 100 respondents users of Eiger products. Data collection was conducted through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results of the study indicate that three independent variables, Consumer Ethnocentrism, Product Knowledge, and Brand Identity, have a positive and significant influence on purchasing decisions. The conclusion this study states that consumers' understanding of the product, a strong brand identity, and a supportive attitude toward local products significantly drive purchasing decisions for Eiger products. These findings recommend that the company continue to strengthen its brand image and consumer education to enhance loyalty and purchase volume.